Home care nurses' attitudes toward computers: a confirmatory factor analysis of the Stronge and Brodt instrument. - Stricklin MLV; Bierer SB; Struk C (CIN: Computers, Informatics, Nursing)
Point-of-care technology for home care use will be the final step in enterprise-wide healthcare electronic communications. Successful implementation of home care point-of-care technology hinges upon nurses' attitudes toward point-of-care technology and its use in clinical practice. This study addresses the factors associated with home care nurses' attitudes using Stronge and Bradt's Nurse Attitudes Toward Computers instrument. In this study, the Nurses Attitudes Toward Computers instrument was administered to a convenience sample of 138 nurses employed by a large midwestern home care agency, with an 88% response rate. Confirmatory factor analysis corroborated the Nurses Attitudes Toward Computers' 3-dimensional factor structure for practicing nurses, which was labeled as nurses' work, security issues, and perceived barriers. Results from the confirmatory factor analysis also suggest that these 3 factors are internally correlated and represent multiple dimensions of a higher order construct labeled as nurses` attitudes toward computers. Additionally, two of these factors, nurses' work and perceived barriers, each appears to explain more variance in nurses' attitudes toward computers than security issues. Instrument reliability was high for the sample (.90), with subscale reliabilities ranging from 86 to .70.